KRITERIA PEMILIHAN JENIS KAYU DALAM PEMBUATAN KAPAL WISATA BERDASARKAN PENGETAHUAN MASYARAKAT KELURAHAN TUKTUK SIADONG KABUPATEN SAMOSIR PROVINSI SUMATERA UTARA - Gultom, Dina Taruli; Evi Sribudiani; Sonia Somadona (Fakultas Kehutanan Universitas Lancang Kuning, 2020)
Forest has an important part in producing a thing which wood or non-timber and environmental services as a buffer zone for living things. Wood is widely used as carpentry wood, wood tools (furniture), building wood (construction), one of which is in shipbuilding. One of them is a tour ship in Tuktuk Siadong area which is a means of transportation provided by private companies as a special means of transportation for tourists. The purpose of this study was to identify the types and criteria of wood used in the manufacture of tour ship based on public knowledge in Tuktuk Siadong Village, Samosir Regency, North Sumatra Province. This research used a survey and sampling method that was determined purposively. Based on the results of interviews conducted priority wood types used by the community as raw material for making tour ship are johar wood (Cassia seamea) and surian wood (Toona sureni). While alternative wood types used are balau wood (Hopea celebica), kempas wood (Koompassia malaccensis) and nangka wood (Artocarpus heterophyllus). The criteria for raw materials for making a tourist ships are having a tree height 20 m, tree diameter 50 cm, wood length 18 m with a level of straightness 80%.